The Economic Development of Asian Countries With Achievement of SDG 8: A Systematic Literature Review - Alya Dwi Pratiwi; Salahudin Salahudin; Syamsulrizal Syamsulrizal; Havidz Ageng Prakoso (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
This study aims to find the correlation between goal 8 of the Sustainable Development Goals (SDGs) and the economic growth of countries in Asia. This study uses the research method applied in this study, the Systematic Literature Review (SLR), which operates about 600 articles of scientific data sourced from the Scopus database in this review, using the Vosviewer application. The research results reveal many essential points in economic growth in achieving the goals of SDG 8. Since there are still many differences in development that support economic growth, the findings of this study are beneficial to a nation, particularly developing countries in Asia that are still lagging in their economies. With the implementation of the SDGs, the expectation is that the Asian countries are still languishing in infrastructure development as support for the product would realize, and economic growth would be distributed. SDG goal 8, "Economic Growth and Jobs Worth it," emphasizes growth in a more inclusive and sustainable economy, in addition to more productive and full employment opportunities and decent work for all. In addition, population growth is also a factor that has an essential role in achieving the expected economic growth, population density in a country will later impact the country's economy if the government takes no action to deal with this.